Georgia at a glance: Abakhazian and South Ossetian conflict - Zafer Süslü (IBSU Scientific Journal (IBSUSJ), 2006)
In modern world ethnic conflict has become one of the biggest problems of the contemporary life. In order to understand ethnic conflict we should understand the difference between nationality and ethnicity. One of the bloody and violent so called ethnic conflicts of 20 century were two conflicts on Georgian territory, these were conflicts in Abkhazia and South Ossetia. Solutions must be found in order to avoid the conflicts in the future throughout the world.
Keywords: 330; Conflict; Abkhazia; South Ossetia; Georgia; Nationality; Ethnicity